Delish Biscotti / Anur Ahza Baharom ... [et al.] - Baharom, Anur Ahza; Abd Razak, Nurlynn Batrisyia; Junid, Nur Amirah; Akmal Azmi, Nurul Izzah; Saharul, Siti Nurnabila Farina (2021)
Delish Biscotti is basically a sole proprietorship company that bakes biscuit for all people. The company biscuits that own by one individual entrepreneur and hire many people to fill the position in this company. The business been operated about 4 years since 2016 and located at Melaka. The objective of this business is that we want to help people open their hearts and minds to each other through our cookies. For us, each biscuit is a small yet exciting opportunity to share a bite and to share a moment. Suitable with our trademark which is “Eat & Repeat”. This trademark explained that our cookies is very addictive as the consumer have the feeling to buy again and crave our cookies. A part from that, the price of our product which is Melted Cadbury Cookies is only at RM 15.00. This product is free from added preservatives and artificial color that can harm and risk the health of our consumer. Therefore, the consumers should not worry about the ingredient we use. We have apply high standard of cleanliness, consideration, and food safety in the production of our biscuits. Last but not least, Delish Biscotti’s company is also committed to delivering a quality experience to its customers. We always find new ways and method on improving the biscuit-baking process, conducting trial after trial to attain the tastiest biscuit before proceeding to mass production. We bake every single piece to our high standards of quality and taste. So, the end user will received at the best quality exactly as the image of cookies we shown in our advertisement. The reason we bake every single piece to our high standards of quality and taste so that the customer will fall in love with our cookies on every single bite.